Excess Wages Tax - Erbas, S. (IMF Working Papers; Working Paper ;, 1995)
Excess wages tax (EWT) is a tax-based incomes policy instrument introduced in many centrally-planned economies and still used in some FSU and Eastern European countries in transition. The main macroeconomic goal of EWT is to curb inflationary pressures by penalizing through taxation the 'excessive' wage awards granted by enterprises in the course of wage and price liberalization. In this paper, effects of EWT on the behavior of a profit-maximizing enterprise under monopsony, its incidence on wages and profits, and its impact on inflation are analyzed. The effect of EWT on an enterprise that maximizes workers' income is also examined with some observations on EWT's impact on managerial behavior. Finally, recent experience with EWT is assessed and compared to that suggested by the model.